Nutritive value of fermented and extruded canola meal as a dietary ingredient for broiler chickens under unheated and heated conditions - Aljuobori, Ahmed Abed Wadi (2014)
The amino acid profile of canola meal (CM) protein compares favorably with that of soybean meal protein. However, it contains antinutritional factors, and high dietary fibre which may limit its utilisation in poultry feeding. Thus, there is a need to investigate possible methods to improve the nutritional value of CM. There is also a concern of feeding CM to poultry under hot climate because of its high fibre content. The present work determined the effects of extrusion and fermentation on the content of various nutrients and anti-nutrients in CM. The response of broiler chickens to various levels of untreated, extruded (EM) and fermented (FCM) CM under unheated and heated conditions were elucidated. The first study was to determine the effect of extrusion process on apparent metabolizable energy (AME), crude protein (CP) and amino acid (AA) digestibility of CM in broiler chickens. The results showed that ECM had greater AME (2595 vs 2243 kcal/kg) compared to CM. Extrusion also significantly enhanced apparent ileal digestibility of CP and some of AA such as Asp, Glu, Ser, Thr and Trp. The second digestibility study was to investigate the potential of Lactobacillus salivarius solid state fermentation for reduction of glucosinolate content in canola meal (CM) as well as the improvement of its nutrient digestibility for broiler chickens. Nutrients ileal digestibility was tested using 42-day-old broilers fed either CM or FCM as the sole source of energy and protein. The digestibility coefficient was improved significantly for crude protein, Met, Cys, Arg, Asp, Glu, and Ser in FCM compared to CM. However, apparent metabolisable energy of CM was not affected by fermentation. Three feeding trials were conducted to determine the effect of various levels of dietary inclusion of untreated CM, ECM and FCM on performance, carcass yield, body temperature and plasma levels triiodothyronine (T3) and tetraiodothyronine (T4) in broiler chickens under chronic heat stress. Treated CM was included in the starter and finisher diets at 0, 10, 20, and 30% from 1 to 35 days of age. All diets were isocaloric and isonitrogenous. From 29 to 35 day an equal number of birds from each dietary group were exposed to either 23±1oC (unheated) or 36±1°C (heated) throughout. Inclusion of untreated of CM at 10% or above retarded weight gain and FCR of broiler chicks during the starter phase. CM can be added up to 30% in the finisher diet of heated chickens without any adverse effect on growth performance but not under unheated condition. Carcass parameters, T3 and T4 were not affected by diet. Heated birds had lower carcass yield and T3. Feeding ECM more than 10% during the starter period retarded growth performance. Under unheated condition, birds can only be fed 10% ECM during day 29 to 35 for optimum performance. However, feeding 30% ECM was not detrimental for WG and FCR of heated chickens. Heat stress reduced percentage of carcass but increased leg meat yield. Diet had negligible effect on broiler carcass yield. Although feeding 20 and 30 % ECM elevated plasma level of T3 in unheated birds, no effect of diet was observed on the hormone concentration in heated birds. Feeding FCM more than 10% during the starter period retarded growth performance. Both unheated and heated broilers can be fed 30% FCM without any detrimental effect on performance from 29 to 35 days of age. There was no significant effect of diet on carcass parameters or T3 and T4. Irrespective of diet, heat treatment reduced carcass weight and T3. In conclusion, the present results suggest that extrusion and fermentation may improve the nutrient availability of CM. However, the optimum levels of ECM and FCM inclusion in the diets of broiler chickens varied according to age and environmental temperature. Cost effectiveness and practicality in terms of application under commercial setting are important factors to be considered in identifying the suitable method of treating CM.